The Restoration of Degraded Lands by Local Communities and Indigenous Peoples - Santini, Nadia S.; Miquelajauregui, Yosune (Frontiers in Conservation Science, 2022)
One of Earth’s foremost ecological challenges is the degradation of land habitats. This degradation is often caused by deforestation and desertification resulting from the unsustainable management of natural resources. Land restoration seeks to reverse this trend and repair ecosystems to better health. Indigenous peoples and local communities have a key role in realising long-term, sustainable land restoration. Local and indigenous communities often have intimate knowledge of the local ecosystems and an interest in preserving ecosystem services. Areas managed by indigenous peoples and local communities especially overlap with remaining intact ecosystems and suffer from less deforestation than unprotected areas. Here, we discuss how the knowledge and engagement of local communities can improve the management, implementation, and monitoring of habitat restoration. However, there are also challenges to land restoration, and scientists and policymakers that can align restoration outcomes with community benefits gained from environmental stewardship and knowledge, are more likely to achieve long-term sustainable restoration success.